Calcium Mobilization by Activation of M3/M5 Muscarinic Receptors in the Human Retinoblastoma - Dae-Ran Kim; Sang Hoon Rah; Joon Hyung Sohn; Byung-Il Yeh; Chang Mann Ko; Jeong Sook Park; Min-Jeong Kim; Joong Woo Lee; In Deok Kong (Elsevier, 2007)
Activation of muscarinic acetylcholine receptors (mAChR) is one of the most important signal transduction pathways in the human body. In this study, we investigated the role of mAChR activation in relation to its subtypes in human retinoblastoma cell-lines (WERI-Rb-1) using Ca2+ measurement, real-time PCR, and Western Blot techniques. Acetylcholine (ACh) produced prominent [Ca2+]i transients in a repeated manner in WERI-Rb-1 cells. The maximal amplitude of the [Ca2+]i transient was almost completely suppressed by 97.3 ± 0.8% after atropine (1 µM) pretreatment. Similar suppressions were noted after pretreatments with thapsigargin (1 µM), an ER Ca2+-ATPase (SERCA) inhibitor, whereas the ACh-induced [Ca2+]i transient was not affected even in the absence of extracellular calcium. U-73122 (1 µM), a PLC inhibitor, and xestospongin C (2 µM), an IP3-receptor antagonist, elicited 11.5 ± 2.9% and 17.8 ± 1.9% suppressions, respectively. The 50% inhibitory concentration of (IC50) values for blockade of a 100 µM ACh response by pirenzepine and 4-DAMP were 315.8 and 9.1 nM, respectively. Moreover, both M3 and M5 mAChRs were prominent in quantitative real-time-PCR. Taken together, the M3/M5 subtypes appear to be the major contributor, leading to intracellular calcium mobilization from the internal store via an IP3-dependent pathway in the undifferentiated retinoblastoma cells. Keywords:: muscarinic receptor, calcium, retinoblastoma